Mapping local patterns of childhood overweight and wasting in low- and middle-income countries between 2000 and 2017 - LBD Double Burden of Malnutrition Collaborators (Nature, 2022)
This article was published in Nature Medicine by Nature [ Copyright © 2020, The Author(s)] and the definite version is available at: https://doi.org/10.1038/s41591-020-0807-6 The Journal's website is at: https://www.nature.com/articles/s41591-020-0807-6